Effect of Preparation Methods on the Adsorption of Glyphosate by Calcined Ca–Al Hydrotalcite - Peng, Guanping (ACS Omega, 2021)
[Image: see text] Calcined Ca–Al hydrotalcites were prepared by the clean method (Ca-LDO-1) and traditional co-precipitation method (Ca-LDO-2), respectively. The effect of the preparation method on the adsorption of glyphosate by calcined Ca–Al hydrotalcites was investigated. The adsorbents were also characterized by X-ray diffraction (XRD), thermogravimetric (TG) analysis, inductively coupled plasma optical emission spectroscopy (ICP-OES), and low-temperature N(2) adsorption–desorption, respectively. Compared with Ca-LDO-2, Ca-LDO-1 had higher specific surface area and pore volume, which caused it to show better adsorption performance and reusability for the adsorbing of glyphosate. In addition, the kinetics and thermodynamics of the adsorption of glyphosate by Ca-LDO-1 were studied. The results showed that it was more consistent with the pseudo-second-order kinetic equation and Langmuir isotherm equation.